Analytical study of some self-referred or state dependent functional equations - El-Sayed, A. M. A.; Hashem, H. H. G.; Al-Issa, S. M. (Methods of Functional Analysis and Topology, 2022)
In this paper, we consider some self reference or state dependent functional equations. Also, we shall discuses a continuous dependence of the solutions of that functional equations on the delay functions. Розглянуто деякі самопосилаючі або залежні за станом функціональні рівняння, та неперервна залежність розв’язків цього функціонального рівняння від функції затримки.